2021
DOI: 10.1097/shk.0000000000001840
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width at Admission Predicts the Frequency of Acute Kidney Injury and 28-Day Mortality in Patients With Acute Respiratory Distress Syndrome

Abstract: To determine the association of red cell distribution width (RDW) at admission with frequency of acute kidney injury (AKI) and 28-day mortality in acute respiratory distress syndrome (ARDS) patients. Methods: Two hundred fifty-eight ARDS patients were investigated in retrospective and prospective studies. The primary outcome was frequency of AKI. The secondary outcome was 28-day mortality. Results: The retrospective study included 193 ARDS patients, of which 67 (34.7%) were confirmed AKI and 76 (39.4%) died wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…During organ transplantation, acute blood loss, or toxic shock, ischemia/reperfusion injury has become an important pathogenic mechanism which leads to acute kidney injury [ 18 ]. As the most important excretory organ in the human body, drugs are often excreted through the kidney, and their massive use or even abuse is likely to cause drug-induced acute kidney injury [ 19 ]. Sepsis complicated with acute kidney injury refers to acute renal parenchymal injury occurring to patients with sepsis, and other factors may cause kidney damage like renal ischemia or nephrotoxic substances are excluded.…”
Section: Introductionmentioning
confidence: 99%
“…During organ transplantation, acute blood loss, or toxic shock, ischemia/reperfusion injury has become an important pathogenic mechanism which leads to acute kidney injury [ 18 ]. As the most important excretory organ in the human body, drugs are often excreted through the kidney, and their massive use or even abuse is likely to cause drug-induced acute kidney injury [ 19 ]. Sepsis complicated with acute kidney injury refers to acute renal parenchymal injury occurring to patients with sepsis, and other factors may cause kidney damage like renal ischemia or nephrotoxic substances are excluded.…”
Section: Introductionmentioning
confidence: 99%
“…24 In previous studies, elevated RDW values were found to be related to prognosis in patients with community-acquired pneumonia (CAP), ARDS and COVID-19. [25][26][27] In a meta-analysis, RDW values were found to be significantly higher in dying COVID-19 patients compared to survivors (95% CI=0.63-1.23; I 2 =85.58%). In addition, elevated RDW values were reported to be associated with the disease severity (30-day mortality, duration of hospital stays and the need for vasopressor support) (95% CI=0.47-0.97; I 2 =89.51%).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically,the progression and overall survival in ARDS is primary determined by the overlapping of excessive systemic in ammatory cascade,alveolar capillary damage, increased permeability and microthrombosis, alveolar epithelial damage, dysregulated coagulation,and reduced or absent of pulmonary surfactant in various degrees (19,48),disturbances of multifarious biological process of synthesis and secretion of in ammatory factors and signal transduction pathways allows for the exploration of potential biomarkers which correlated strongly with risk of death or prognosis of ARDS (49).Considering that PT and PTT as biomaker involved in the pathway of coagulation and brinolysis,we further explore the ROC curves of PT and PTT for predicting the 28-day mortality of patients with ARDS.It turned out that PT and PTT have lager AUCs when compared with PLT,which might also can be a potentially important object in future clinical research to identify individuals with poor prognosis,and a combination of PLT and PT may be attractive in order to provide better diagnostic and prognostic capacity of ARDS.A accumulating body of studies indicated that red blood cell distribution width as a biomarker of oxidative stress and in ammation maintained association with the prognosis of ARDS (50)(51)(52)(53).Our data also obtained the similar results,but a single RDW does not fully re ect the in ammatory status,the composites of RDW and PLT may take it a step further identify the relationship among the in ammatory conditions and prognosis,therefore,prospective investigation is necessary to validate the impact of combination of RDW and PLT on predicting ARDS.…”
Section: Discussionmentioning
confidence: 99%